2019
DOI: 10.3390/cells8070683
|View full text |Cite
|
Sign up to set email alerts
|

The Detection and Morphological Analysis of Circulating Tumor and Host Cells in Breast Cancer Xenograft Models

Abstract: Hematogenous dissemination may occur early in breast cancer (BC). Experimental models could clarify mechanisms, but in their development, the heterogeneity of this neoplasia must be considered. Here, we describe circulating tumor cells (CTCs) and the metastatic behavior of several BC cell lines in xenografts. MDA-MB-231, BT-474, MDA-MB-453 and MDA-MB-468 cells were injected at the orthotopic level in immunocompromised mice. CTCs were isolated using a size-based method and identified by cytomorphological criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…The effectiveness of the developed targeted agents for solid tumors as well as metastasis treatment was evaluated using mouse model with xenograft tumors derived from BT-474 cell line. It was recently shown that ductal carcinoma cell line BT-474 has a great potential as cancer model with spontaneous metastasis [ 40 , 41 , 42 , 43 ]. It was shown BT-474-based tumors can form metastases in lymph nodes, lungs or spleen with various frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the developed targeted agents for solid tumors as well as metastasis treatment was evaluated using mouse model with xenograft tumors derived from BT-474 cell line. It was recently shown that ductal carcinoma cell line BT-474 has a great potential as cancer model with spontaneous metastasis [ 40 , 41 , 42 , 43 ]. It was shown BT-474-based tumors can form metastases in lymph nodes, lungs or spleen with various frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides descriptive approaches, functional CTC assays exist (eg, the EPithelial ImmunoSPOT [EPISPOT] that is based on the measurement of secreted protein by viable CTCs after short‐term culture) 23 . In patients with extremely high CTC counts (usually >100 per mL blood), the functional properties of CTCs can be further investigated by the establishment of long‐term cell culture/cell lines or the development of xenograft models 24,25 (Figure 1A). However, the establishment of these models requires many months and the efficacy rates are very low, which makes them unsuitable as tool for clinical trials or decision‐making in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is technically very difficult however, as CTCs released as the primary tumour is manipulated would reach peripheral targets very rapidly and be removed from the circulation. A study examining CTCs in a murine breast cancer model found that there were only between 1 and 7 CTCs remaining per mL of blood 1 hour following an intravenous injection of 10 6 or 2 × 10 6 MDA-MB-231 cells in the lateral tail vein of the mice [34]. Such a rapid removal of cells from the circulation makes the timing of surgical excision and subsequent blood sampling (requiring cardiac puncture and sacrifice of the animal) to ensure capture of an adequate number of CTCs for Src evaluation extremely challenging.…”
Section: Discussionmentioning
confidence: 99%